Determinants Of Sharia Fintech Adoption And Its Impact On Financial Inclusion Among Msmes In Timika, Papua - Junarti Junarti; Muliana Muis (IAIN Langsa, 2026)
This study aims to analyze the factors influencing the intention to adopt Sharia fintech and its impact on financial inclusion among MSME actors in Timika, Papua. This study employs a quantitative approach using the Structural Equation Modelling–Partial Least Squares (SEM-PLS) method and involves 37 respondents from MSMEs. The independent variables comprise Digital Infrastructure and Capacity Access, Financial Literacy, Islamic Knowledge, and Regulatory and Ecosystem Support. In contrast, the dependent variables include the adoption intention for Islamic Fintech and Financial Inclusion through Islamic Fintech. The study found that Regulatory and Ecosystem Support had a positive and significant effect on Adoption Intention, whereas Digital Infrastructure and Financial Literacy did not have a significant effect. In addition, Adoption Intention has a significant effect on Financial Inclusion and mediates the relationship between regulatory support and Financial Inclusion. These findings confirm that the success of sharia fintech adoption in 3T regions, such as Timika, is determined more by regulatory clarity, system security, and ecosystem support than technical factors. This research contributes to the understanding of the adoption of Sharia fintech in developing regions and offers policy recommendations to strengthen Islamic financial literacy and an inclusive digital ecosystem.